Computer vision–ACCV 2014 : 12th Asian Conference on Computer Vision, Singapore, Singapore, November 1-5, 2014, revised selected papers /: 12th Asian Conference on Computer Vision, Singapore, Singapore, November 1-5, 2014, revised selected papers. ([2015]) - Unknown
No abstract available